Zrównoważony rozwój w strategiach Unii Europejskiej - Borys, Tadeusz (Sustainable Development : the European Union Strategies, 2005)
In the article it has been assumed that both the principles of permanence and revealing their connection with ethical concepts, as well as the quality of life, are of significant importance for the identification of these relations. Sources of narrow and broad interpretation of sustainable development concept were considered together with basic consequences of their choice based, among others, on an example of the European Union strategic documents - the Lisbon Strategy and the Strategy of Sustainable Development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 36-48